62.7k views
3 votes
Help!?!?!?!??!!!!!!!!!!!!!!

Help!?!?!?!??!!!!!!!!!!!!!!-example-1

2 Answers

5 votes

D.
(21 \: b)/(10) - 48

Explanation:


- 6( (1)/(4) b+ 10) + 4( (9)/(10)b + 3) \\ = ( - 6 \: b)/(4) - 60 + (36 \: b)/(10) + 12 \\ = ( - 3 \: b)/(2) + (18 \: b)/(5) - 60 + 12 \\ = ( - 3 \: b * 5)/(2 * 5) + (18 \: b * 2)/(5 * 2) - 48 \\ = ( - 15 \: b + 36 \: b)/(10) - 48 \\ = (21 \: b)/(10) - 48


\circ \: \: { \underline{ \boxed{ \sf{ \color{green}{Happy\:learning.}}}}}∘

User Rafael Oltra
by
5.0k points
4 votes

Answer:

Explanation:

Answer d) looks good

User AlanB
by
5.0k points